2012
DOI: 10.1002/dc.22826
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal seminoma: A case report with special emphasis on SALL4 as a new immunocytochemical marker

Abstract: Cytological diagnosis is a valuable method for detection of mediastinal tumors, and recent reports have shown the usefulness of fine-needle aspiration cytology for diagnosis of mediastinal tumors, including germ cell tumors. We report a case of mediastinal seminoma diagnosed intraoperatively by cytological examination of cystic fluid containing tumor cells. An anterior mediastinal tumor with cystic component was incidentally found in a 28-year-old Japanese male. Cytological examination of the cystic fluid at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In solid tumors, SALL4 was first studied in germ cell tumors, where it is a sensitive diagnostic marker for primary central nerve system (CNS) germ cell tumors 66 , testicular germ cell tumors 67 , primary extragonadal germ cell tumors 101102 , mediastinal seminoma 103,104 , ovarian malignant germ cell tumor 105 , and metastatic germ cell tumors 106 . In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 .…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…In solid tumors, SALL4 was first studied in germ cell tumors, where it is a sensitive diagnostic marker for primary central nerve system (CNS) germ cell tumors 66 , testicular germ cell tumors 67 , primary extragonadal germ cell tumors 101102 , mediastinal seminoma 103,104 , ovarian malignant germ cell tumor 105 , and metastatic germ cell tumors 106 . In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 .…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…A case of mediastinal seminoma misinterpreted as anaplastic thyroid carcinoma has also been reported [123]. Cell block preparations for immunohistochemical studies are helpful as seminomas will be positive for PLAP, CKIT, OCT3/4, SOX17, and SALL4 and negative for CD30 and AFP [119,[123][124][125]. Weissferdt and colleagues demonstrated that mediastinal seminomas can have CAM5.2 expression, albeit focally compared with thymomas and thymic carcinomas, which have diffuse staining.…”
Section: Seminomamentioning
confidence: 99%